Modelling of linear and non-linear two-body wave energy converters under regular and irregular wave conditions. (March 2020) - Ji, Xueyu; Shami, Elie Al; Monty, Jason; Wang, Xu
Abstract: This paper studies a two-body wave energy converter oscillating in heave with a floating body of variable geometry connected to a submerged body, which is designed for the specific ocean wave condition with wave excitation frequencies ranging from 0.08 Hz to 0.12 Hz. The study focuses on the parameter and non-linear effects of the converter. Taguchi method has been applied to investigate the system model parameters' influences on the maximum average power output. ANSYS AQWA is employed to obtain the hydrodynamic parameters for calculating the output power. Both linear and non-linear dynamic models of the two-body wave energy converter will be analysed and simulated in both the time and frequency domains. The new scientific contribution is identifying the best parameter combination of the two-body wave energy converter for irregular wave excitations for the Australian ocean wave conditions, evaluating and comparing the output power of both linear and non-linear dynamic models of the two-body wave energy converter. Another contribution is having established a non-linear model for those buoys of non-uniform shape in vertical direction which has largely improved the simulation accuracy in comparison with a linear model where the buoy hydrostatic forces were simulated using a linear approximation model. The most important results are having found that the power-take-off stiffness coefficient and submerged body geometry are the most important parameters to change for the largest output power. It is found that the significant wave height has very little influence on the efficiency whilst the variations of the peak period of the irregular wave can change the efficiency largely. The non-linear hydrostatic force is found to have considerable effects on the buoy's dynamic performance. The best combination of the system parameters for the harvesting performance has been identified using the Taguchi method, which produces a peak efficiency of 51% in irregular waves. This manuscript aims to disclose the parameter effect of a two body WEC on its performance using Taguchi method and to provide a guide for industry and research community for designing a good two body WEC. Graphical abstract: The effect of the seven selected parameter variables on the maximum average power output for a regular wave excitation. Image 1 Highlights: A two-body wave energy converter is designed for the Australian ocean wave conditions. ANSYS AQWA is employed for the hydrodynamic simulation and analysis. Taguchi method is applied for a parameter study of the two-body wave energy converter. The output power is evaluated for both linear and non-linear dynamic models of the two-body wave energy converter. The most important parameters of power-take-off stiffness coefficient and submerged body geometry and best parameter combination have been identified for irregular wave excitations.